Influencia de variables de formulación en la viscosidad de emulsiones de surfactante aniónico-aceite-agua - Gerson Chávez; Irán Parra; Milangel Luzardo; Bélgica Bravo; Nacarid Delgado; Nelson Márquez (Química Nova, 2014)
Phase transition and viscosity behavior of emulsified systems were studied after modifying their physicochemical formulation. Effects of concentration and nature of salts and n-alcohols, and water/oil relation on the rheological properties of emulsions were also studied. Pre-equilibrated systems were emulsified according to an agitation procedure, and the viscosity (cP) was measured at different shear rates ranging from 1 to 300 s-1. The phase behavior, as well as the emulsion type based on electrolytic conductivity, was observed. Several interpretations of the flow and viscosity curves of emulsions were made through the estimation of rheological parameters such as consistency index "k" and behavior index "n".